The Effect Of Children's Value On Family Planning Participation On Mothers Of Couples Of Reproductive Age - Haris Muda Rambe (International Archives of Medical Sciences and Public Health, 2020)
Introduction: Family planning determines the quality of the family because it has the potential to save women's lives and improvetheir health status, especially by preventing unwanted pregnancies,birth spacing, and reducing the risk of infant mortality. The low levelof family planning acceptance is caused by the influence of children'sgrades. The purpose of this study was to determine the influence ofchildren's cultural, economic, social, and psychological values on theparticipation of women of childbearing age in the Family Planningprogram in the working area of the Pijokorling Public Health Center.Methods: The population of this cross-sectional observational studyconsisted of 825 mothers in couples of childbearing age, and 92 ofthem were randomly selected to be used as samples for this studyusing simple random sampling technique. This study collects datathrough observation and interviews. Results: Chi-square test andmultiple logistic regression were used to analyze the data. Thefindings of this study indicate that there is a relationship betweenchildren's cultural values ( p<0.001 ), children's economic values (p =0.001), children's social values (p = 0.034), and children's socialvalues (p = 0.034). psychological value of children (p = 0.020) andparticipation of mothers of reproductive age couples in the FamilyPlanning program. Conclusion: what is obtained is that children'scultural values have the greatest influence on the participation ofwomen of childbearing age in the Family Planning program in theworking area of the Pijorkoling Health Center. Health workers,especially those from the BKKBN (National Family PlanningCoordination Agency) in the working area of the Pijorkoling HealthCenter, Padangsidimpuan District, are expected to continue educatingEFA mothers about the importance of participating in the FamilyPlanning Program through health education which emphasizes thatwomen of childbearing age (EFA) are responsible. on their ownreproductive health.